Potential immunomodulatory activity of Phyllanthus niruri aqueous extract on macrophage infected with Streptococcus sanguinis - Hutomo, Suryani; Putri, Denise Utami; Suryanto, Yanti Ivana; Susilowati, Heni (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Streptococcus sanguinis is an oral commensal bacterium commonly found in periodontal lesions and deep abscesses that are usually dominated by anaerobic bacteria. As an important causative agent of systemic diseases, and with the increasingly numerous cases of antimicrobial resistance, some means of modulating the immune response to bacterial infection is thus necessary. Phyllanthus niruri Linn is widely used as a medicinal herb to both prevent and treat disease and demonstrates immunomodulatory properties. Purpose: This study aimed to observe the potential for aqueous extract of Phylanthus niruri to induce macrophage proliferation and NO production following S. sanguinis infection. Methods: Macrophages were isolated from the peripheral blood of healthy subjects, stimulated with P. niruri aqueous extract in graded doses and infected with S. sanguinis ATCC 10556 bacterial suspension. Cell proliferation and nitric oxide release was observed at 24 and 48 hours to determine macrophage activities. Results: NO production and cell proliferation started to increase upon 50 and 100µg/ml P niruri respective stimulation. Statistical analysis using One-way Anova demonstrated a significant difference of cell proliferation after stimulation with P. niruri aqueous extract at various doses (p<0.05). Conclusion: P. niruri aqueous extract induced macrophage proliferation and NO secretion upon S sanguinis infection, showing potential antibacterial and immunomodulatory activities. At the same concentrations, NO production and macrophage were higher at 48 hours than at 24 hours.